The roles of ubiquitin–proteasome system and regulator of G protein signaling 4 in behavioral sensitization induced by a single morphine exposure. Issue 3 (15th February 2023) - Wang, Yanting; Hou, Xingzi; Wei, Shoupeng; Yan, Jiaqing; Chen, Zhe; Zhang, Mingyu; Zhang, Qingying; Lu, Yingyuan; Zhang, Qingjie; Zheng, Tiange; Jia, Jingyi; Dong, Bin; et al.
Abstract: Aims: Opioid addiction is a major public health issue, yet its underlying mechanism is still unknown. The aim of this study was to explore the roles of ubiquitin–proteasome system (UPS) and regulator of G protein signaling 4 (RGS4) in morphine‐induced behavioral sensitization, a well‐recognized animal model of opioid addiction. Methods: We explored the characteristics of RGS4 protein expression and polyubiquitination in the development of behavioral sensitization induced by a single morphine exposure in rats, and the effect of a selective proteasome inhibitor, lactacystin (LAC), on behavioral sensitization. Results: Polyubiquitination expression was increased in time‐dependent and dose‐related fashions during the development of behavioral sensitization, while RGS4 protein expression was not significantly changed during this phase. Stereotaxic administration of LAC into nucleus accumbens (NAc) core inhibited the establishment of behavioral sensitization. Conclusion: UPS in NAc core is positively involved in behavioral sensitization induced by a single morphine exposure in rats. Polyubiquitination was observed during the development phase of behavioral sensitization, while RGS4 protein expression was not significantly changed, indicating that other members of RGS family might be substrate proteins in UPS‐mediated behavioral sensitization. Abstract : (1) ubiquitin‐proteasome system positively participates in the establishment of behavioral sensitization; (2) the expression of regulator of G protein signaling 4 was not changed during the development of behavioral sensitization; 3) the roles of other family members of regulators of G protein signaling in opioid addiction and their relations with UPS are worth being further explored